INTEGRATING SCIENCE CONCEPT IN ALI ABDUL HALIM INTERPRETATION FOR CHARACTER EDUCATION IN ISLAMIC ELEMENTARY SCHOOLS - Siregar, Parulian; Arif, Mahmud (PIONIR: JURNAL PENDIDIKAN, 2024)
The integration of scientific concepts in Ali Abdul Halim interpretation of character education in Islamic elementary schools is important because it is able to bridge understanding between modern science and Islamic values. By examining this interpretation, we can find a relevant approach to integrating scientific knowledge into a religious-based character education curriculum, thereby producing students who are not only academically intelligent but also have strong morals and ethics. This research aims to explore science concepts in Ali Abdul Halim interpretation of the Qur'an and their relevance to character education in Islamic elementary schools. Additionally, the study examined how the integration of these science concepts could be applied to character education. A descriptive qualitative methodology with a library research approach was utilized. Data sources included Ali Abdul Halim exegesis texts, books, and articles on character education. Data collection was achieved through document analysis and was thematically analyzed, categorized, interpreted, and comprehensively concluded. The findings describe the significance of integrating scientific knowledge with the understanding of Qur'anic verses using a holistic approach that incorporates linguistic, historical, and other scientific aspects. Ali Abdul Halim interpretation integrates the understanding of the Qur'an with modern science across various disciplines. His exegesis emphasizes the importance of character education, focusing on the development of good morals, and the roles of family and environment. His educational concept for elementary education merges Islamic values with modern education through active learning methods, linking science with the meanings of the Qur'an to enhance academic understanding and positive character formation.Keywords: Integration of science, Interpretation of Ali Abdul Halim, Character education.